2018
DOI: 10.3390/su10113997
|View full text |Cite
|
Sign up to set email alerts
|

Social Valuation of Genebank Activities: Assessing Public Demand for Genetic Resource Conservation in the Czech Republic

Abstract: The use of diverse genetic resources to breed improved crop varieties has been a key driver of agricultural productivity improvements in the past century. At the same time, the adoption of modern varieties has contributed to substantial loss of traditional varieties. In this analysis, we estimate the social value provided by several proposed crop diversity conservation programs to be carried out by the Czech genebank system. We use a double-bounded dichotomous choice model to estimate the willingness-to-pay (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…We consider this source of potential bias acceptable, since a questionnaire survey will likely include 'a balanced and effective presentation of information' (Johnston et al 2017)), and following the practice of recent stated preference work investigating the valuation of genetic resource conservation (Tienhaara et al 2019). Similar to the results found by Tyack and Ščasný (2018), we found that respondents who had heard about a genebank beforehand were more likely to contribute to a conservation fund. These two samples are not however the same in terms of their demographic characteristics: respondents who heard about a genebank were found more likely to be males, to be more highly educated, older than 30 years old, city dwellers, gardeners, and to think that investments in adaptation in the agriculture sector are important (see Tyack and Ščasný 2018).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We consider this source of potential bias acceptable, since a questionnaire survey will likely include 'a balanced and effective presentation of information' (Johnston et al 2017)), and following the practice of recent stated preference work investigating the valuation of genetic resource conservation (Tienhaara et al 2019). Similar to the results found by Tyack and Ščasný (2018), we found that respondents who had heard about a genebank beforehand were more likely to contribute to a conservation fund. These two samples are not however the same in terms of their demographic characteristics: respondents who heard about a genebank were found more likely to be males, to be more highly educated, older than 30 years old, city dwellers, gardeners, and to think that investments in adaptation in the agriculture sector are important (see Tyack and Ščasný 2018).…”
Section: Discussionsupporting
confidence: 87%
“…In addition, we find an aggregate WTP across the region of South Moravia of USD $160,000 annually to support pre-breeding activities, demonstrating that preferences are not homogenous across the country. Our results show that Czech citizens at least state that they are willing to support further investment in public agricultural research, conservation activities to increase the number of conserved wild species, and characterization and evaluation efforts to provide better information about the national genebank holdings, though their WTP for non-core genebank activities is lower than that previously estimated for the conservation of crop diversity in general (Tyack and Ščasný 2018).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…This is not only the case for national, regional, or local foods, particularly tasty foods, and organic foods [30][31][32], but also traditional or old vegetable or fruit varieties or animal breeds, as they are typically associated with a particular locality, region or country, cultural heritage and exceptional sensory characteristics [27,[33][34][35][36][37][38][39]. In fact, a recent study by Tyack and Ščasný [40] shows, that consumers are even willing to pay for ex-situ conservation of genetic resources.…”
mentioning
confidence: 99%
“…Since then, we find only a few studies that explore the value of genebanks in the peer-reviewed literature, and these are not directly related to agricultural development in lower income countries. Xepapadeas et al (2014) explored the insurance value of the Greek genebank, and an article by Tyack and Ščasný (2018) applied stated preference methods to value accessions in the Czech genebank. Meanwhile, the technical and operational management of genebanks progressed enormously.…”
mentioning
confidence: 99%